2023
DOI: 10.1146/annurev-pathol-042320-110411
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Consequences of Red Blood Cell Alloimmunization

Abstract: While red blood cell (RBC) transfusion is the most common medical intervention in hospitalized patients, as with any therapeutic, it is not without risk. Allogeneic RBC exposure can result in recipient alloimmunization, which can limit the availability of compatible RBCs for future transfusions and increase the risk of transfusion complications. Despite these challenges and the discovery of RBC alloantigens more than a century ago, relatively little has historically been known regarding the immune factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 160 publications
0
12
0
Order By: Relevance
“…Despite the frequency with which ABO(H) antigens and corresponding anti-ABO(H) antibodies are tested clinically ( Storry and Olsson, 2009 ; Watkins, 2001 ), surprisingly little is known regarding the factors that drive their development. Unlike alloantibody formation that occurs following RBC-induced alloantigen exposure ( Arthur et al., 2017 , 2022a , 2022a ; Arthur, 2023 ; Mener et al., 2018b ; Patel et al., 2018b ; Stowell et al., 2013a ; Zerra et al., 2021 ), anti-ABO(H) antibodies form spontaneously within the first few months of life. Anti-A and anti-B antibodies are typically detectable at 4–6 months of age, peaking between 5 and 10 years of age ( Hillyer et al., 2009 ).…”
Section: Abo Blood Group Systemmentioning
confidence: 99%
“…Despite the frequency with which ABO(H) antigens and corresponding anti-ABO(H) antibodies are tested clinically ( Storry and Olsson, 2009 ; Watkins, 2001 ), surprisingly little is known regarding the factors that drive their development. Unlike alloantibody formation that occurs following RBC-induced alloantigen exposure ( Arthur et al., 2017 , 2022a , 2022a ; Arthur, 2023 ; Mener et al., 2018b ; Patel et al., 2018b ; Stowell et al., 2013a ; Zerra et al., 2021 ), anti-ABO(H) antibodies form spontaneously within the first few months of life. Anti-A and anti-B antibodies are typically detectable at 4–6 months of age, peaking between 5 and 10 years of age ( Hillyer et al., 2009 ).…”
Section: Abo Blood Group Systemmentioning
confidence: 99%
“…This was in part due to differences in anti-A and anti-B antibody production based on polymorphic ABO(H) blood group status that had been recognized for over a century 52 . While RBC polymorphisms are certainly not limited to ABO(H) antigens and antibodies can certainly be generated against other alloantigens 53 59 , the development of antibodies against these structures are unique in that they spontaneously form in the first few months of life 17 , 60 , 61 . Although a variety of hypotheses have existed regarding the role of microbes in the genesis of anti-ABO(H) antibodies 62 , early studies suggested that several microbes exist that can decorate themselves in blood group-like antigens 52 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent with the immune suppression from splenic hypofunction/asplenia, individuals with SCD are in a proinflammatory state at baseline, likely due to chronic haemolysis, TLR4 signalling through free heme and complement activation, all of which can alter innate and adaptive immunity. 2,14,15 Future studies to examine cytokine production, complement activation and other changes in baseline immune activity at the time of vaccination may shed light on the possibility that the pro-inflammatory background offsets the immune suppression from splenic hypofunction/ asplenia resulting in enhanced magnitude and kinetics of the IgG response in SCD. 1,2 Additional interactions between mRNA vaccine, SARS-CoV-2 virus and SCD pathophysiology may also play a role and deserves more mechanistic investigation.…”
Section: Discussionmentioning
confidence: 99%